Pemberdayaan Mahasantri Ma’had Fastabikhul Khoirot, Kembaran melalui Pelatihan Budidaya Melon secara Hidroponik - Darodjat, Darodjat; Endiyono, Endiyono; Pribadi, Teguh; Surya, Mintaraga Eman; Mustofa, Yongki Fajar; Winata, Tri Aldi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
A melon is a horticultural commodity that has high economic value and much demand by the community. The introduction of modern cultivation technology, such as hydroponics, is an added value for the mahasantri (Islamic boarding school students). The mastery of hydroponic melon cultivation techniques is a provision for mahasantri to develop a community economic empowerment model in pesantren. However, hydroponic melon cultivation training has never been conducted at Ma'had Fastabhikul Khoirot. This training was conducted to increase the knowledge of mahasantri about hydroponic melon cultivation. A total of 18 participants engaged in this training, which included material presentation, pre-tests, and post-tests, as well as discussions on hydroponic melon cultivation. Evaluation results indicated a positive outcome, with nearly half of the participants asking questions. There was a knowledge improvement among participants regarding hydroponic melon cultivation, ranging from 10-25%. To further develop the student's skills in this area, practical sessions and field trips focusing on hydroponic melon cultivation should be implemented.